SATISFACTION ON LEARNING EFL IN MAKASSAR: STUDENTS PERCEPTION TO WORK MECHANISM OF ENGLISH TEACHER - Fansury, Andi Hamzah (Teaching English as a Foreign Language Overseas Journal, 2023)
The focus of this study to investigate the satisfaction on learning EFL based on students’ perception to work mechanism of English teacher. Qualitative method used in this research. There were 360 students from some senior high school in Makassar as population in this research with total number of samples were 30 students taken by using purposive sample. The research instruments were interview, and questionnaire. The work Mechanism of English teacher has walked better. That can be analyzed by pursuant of data field from students’ perception that English teacher in bringing the materials have used assorted of method, using planning in teaching, owning ability to manage the class better, and discipline in running the duty. But based on the data obtained in the field, there are still some teachers using conventional methods that make students feel bored in class. After conducted this research, it is expected that the policies of stakeholders, especially in schools so that in the future the learning process will run better and the quality of teachers will be better so that the output obtained is far better than before